EVALUATION OF THE ANTIMICROBIAL PROPERTY OF Eugenia aromatica (L. bali) AND Myristrica fragrans (L.) AGAINST THE GROWTH OF MICROORGANISMS ASSOCIATED WITH DANDRUFF (Malassezia restricta AND Propionibacterium acne) - admin, HAMMA I. I.; MAIGARI I. A.,,; MAIRO MUSA, MARYAM; GIMBA A. M.,; ALHAJI UMAR, INUWA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
This work was aimed at assessing the antimicrobial activities of Eugenia aromaticum and Myristic fragrans buds and seeds extracts on Propionibacterium acne and Malassezia restricta causing dandruff infection. The microbial strains were obtained from the Microbiology Laboratory of the Federal teaching hospital, Gombe. The phytochemical constituents of the plant extracts and antimicrobial testing of the extracts on bacterial and fungal strains were carried out using agar well diffusion method. The determination of the minimum inhibitory concentration (MIC) of the extracts were carried out using broth dilution method. Analysis of Variance (ANOVA) test was used to analyze the data obtained to determine if there was significant difference between the aqueous, n-hexane and chloroform extracts used. The phytochemical screening revealed the presence of alkaloids, tannins, saponins, flavonoids, steroids and glycosides in both plant extracts. The result showed that all the extracts were efficient against the growth of M. restricta and P. acne at all concentration. Aqueous plant extract shows highest zone of inhibition against the tested bacterial and fungal isolate. The minimum inhibitory concentration (MIC) of M. fragrans extracts; aqueous, n-hexane and chloroform against M. restricta was determined at 0.5mg/ml, 5mg/ml, and 50mg/ml concentration respectively and that of P. acne was determined at 5mg/ml for all the plants extracts. The MIC of E. aromaticum plant extracts were at 0.5mg/ml, 5mg/ml and 50mg/ml for aqueous, n-Hexane and chloroform extracts respectively against M. restricta and P. acne. The extract of M. fragrans and E. aromaticum inhibits the growth of M. restricta and P. acne to a certain extent. Hence have antimicrobial potential which may be helpful in the management of dandruff infection.